Contemporary management of fibrolamellar hepatocellular carcinoma: diagnosis, treatment, outcome, prognostic factors, and recent developments - Kassahun, Woubet Tefera (World J Surg Oncol, 2016)
Fibrolamellar hepatocellular carcinoma (FL-HCC) is a malignant liver tumor which is thought to be a variant of conventional hepatocellular carcinoma (HCC). It accounts for a small proportion of HCC cases and occurs in a distinctly different group of patients which are young and usually not in the setting of chronic liver disease. The diagnosis of FL-HCC requires the integration of clinical information, imaging studies, and histology. In terms of the treatment options, the only potentially curative treatment option for patients who have resectable disease is surgery either liver resection (LR) or liver transplantation (LT). When performed in a context of aggressive therapy, long-term outcomes after surgery, particularly liver resection for FL-HCC, were favorable. The clinical outcome of patients with unresectable disease is suboptimal with median survival of less than 12 months. The aim of this review is to update the available evidence on diagnosis, treatment options, outcome predictors, and recent developments of patients with this rare disease and to provide a summarized overview of the available literature.